Food Safety Study in Terms of Formaldehyde Content and Bacterial Contamination Levels of Cob Pindang Fish in Simo Gunung and Balong Sari Traditional Markets, West Surabaya - Nur Hanifah; Yulistiani, Ratna; Putra, Andre Yusuf Trisna (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Formalin is a food additive that has been banned by BPOM but can still be found in food products. This study aims to determine: 1) the food safety of pindang fish sold in traditional markets in West Surabaya in terms of formalin content and bacterial contamination; 2) the relationship between the hygienic conditions of traders and formalin content on the level of bacterial contamination; and 3) the bacterial growth patterns during room temperature storage of formalin-positive and formalin-negative tuna pindang fish. This is a cross-sectional study with a sampling technique of saturation. A qualitative formalin test was conducted using a formalin test instrument. The results indicated that 88.23% (15 of 17 samples) of cob pindang contained formalin and that 64.7% (11 of 17 samples) exceeded the SNI 2717: 2017 maximum limit for total microorganisms. There was a significant correlation between the level of bacterial contamination and the hygienic conditions of traders. There is no correlation between formalin concentration and bacterial contamination level. The pattern of bacterial proliferation did not differ between formalin-positive and negative cob pindang fish